Fatal anaphylaxis with neuromuscular blocking agents: a risk factor and management analysis. Issue 7 (10th May 2014) - Reitter, M.; Petitpain, N.; Latarche, C.; Cottin, J.; Massy, N.; Demoly, P.; Gillet, P.; Mertes, P. M.; the French Network of Regional Pharmacovigilance Centres
Abstract Background Anaphylactic reactions to neuromuscular blocking agents (NMBAs) can be severe and even fatal. Our aim was to evaluate mortality rate in France from anaphylactic reactions to NMBAs, to identify risk factors for a fatal outcome, and to describe management of the cases that proved fatal. Methods The French National Pharmacovigilance Database was queried for reports of NMBA anaphylaxis that occurred between January 2000 and December 2011. A questionnaire was sent to regional pharmacovigilance centers to obtain further information on the management of cases with a fatal outcome. Results Two thousand and twenty‐two cases of NMBA hypersensitivity were retrieved, of which 84 were fatal (4.1%). Among the 1247 cases of severe NMBA anaphylaxis (grades 3 and 4), independent risk factors associated with a fatal outcome in a multivariate analysis were male gender (female gender: OR = 0.4; 95% CI 0.2–0.7; P = 0.0004), an emergency setting (OR = 2.6; 95% CI 1.5–4.6; P = 0.0007), a history of hypertension (OR = 2.5; 95% CI 1.5–4.4; P = 0.0010) or of other cardiovascular disease (OR = 4.4; 95% CI 2.4–8.1; P < 0.0001), obesity (OR = 2.4; 95% CI 1.1–5.3; P = 0.0376), and ongoing beta‐blocker treatment (OR = 4.2; 95% CI 1.8–9.8; P = 0.0011). All 31 patients with a fatal outcome received epinephrine in a titrated manner according to international guidelines. Conclusion Obese males with a history of cardiovascular disease receiving ongoing beta‐blocker treatment and undergoing surgery in an emergency setting were at high risk of a fatal outcome after NMBA‐induced anaphylaxis. Some epinephrine‐resistant cases may play a role in our high mortality rate. New therapeutic approaches need to be developed to treat these cases.